Landscape and evolutionary dynamics of terminal repeat retrotransposons in miniature in plant genomes. Issue 1 (December 2016) - Gao, Dongying; Li, Yupeng; Kim, Kyung; Abernathy, Brian; Jackson, Scott
Abstract Background Terminal repeat retrotransposons in miniature (TRIMs) are a unique group of small long terminal repeat retrotransposons that are difficult to identify. Thus far, only a few TRIMs have been characterized in the euphyllophytes, and their evolutionary and biological significance as well as their transposition mechanisms are poorly understood. Results Using a combination of de novo and homology-based methods, we annotate TRIMs in 48 plant genome sequences, spanning land plants to algae. The TRIMs are grouped into 156 families including 145 that were previously undefined. Notably, we identify the first TRIMs in a lycophyte and non-vascular plants. The majority of the TRIM families are highly conserved and shared within and between plant families. Unlike other long terminal repeat retrotransposons, TRIMs are enriched in or near genes; they are also targeted by sRNAs between 21 and 24 nucleotides in length, and are frequently found in CG body-methylated genes. Importantly, we also identify putative autonomous retrotransposons and very recent transpositions of a TRIM element inOryza sativa . Conclusions We perform the most comprehensive analysis of TRIM transposons thus far and report that TRIMs are ubiquitous across plant genomes. Our results show that TRIMs are more frequently associated with large and CG body-methylated genes that have undergone strong purifying selection. Our findings also indicate that TRIMs are likely derived from internal deletions of large long terminal repeat retrotransposons. Finally, our data and methodology are important resources for the characterization and evolutionary and genomic studies of long terminal repeat retrotransposons in other genomes.